1996
DOI: 10.1002/crat.2170310511
|View full text |Cite
|
Sign up to set email alerts
|

Research of the Central Core in Bi12SiO20Crystals

Abstract: The structure of the so‐called “central core” within Czochralski grown Bi12SiO20 crystals is investigated by the laser projection. A finer structure with a number of optical inhomogeneities with irregular forms and sizes about 2–3 μm is observed within the core. The conditions for facet growth and absorption of impurities on the facets are described. Positron lifetime measurements are carried out within and outside the core. The results show a higher concentration of defects in regions within the core. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Some authors [5] explain the central core as a consequence of the so-called "facet growth" when facets are formed during the crystal growth process that preferentially absorb photochromic impurities, thus forming the so-called "growth bands". Such problems usually arise due to changes in parameters that are important for the growth process like distortion of the thermal field, and hence fluctuations in the melt composition, undercooling, metastable phases, or changes in the impurity distribution coefficients [6][7][8][9][10][11]. Our Raman spectroscopy studies on undoped BSO crystals showed no increased impurity concentration and the differences in the measured spatially resolved Raman spectra can be explained with only slight local misorienations in the crystal lattice [12].…”
Section: Introductionmentioning
confidence: 97%
“…Some authors [5] explain the central core as a consequence of the so-called "facet growth" when facets are formed during the crystal growth process that preferentially absorb photochromic impurities, thus forming the so-called "growth bands". Such problems usually arise due to changes in parameters that are important for the growth process like distortion of the thermal field, and hence fluctuations in the melt composition, undercooling, metastable phases, or changes in the impurity distribution coefficients [6][7][8][9][10][11]. Our Raman spectroscopy studies on undoped BSO crystals showed no increased impurity concentration and the differences in the measured spatially resolved Raman spectra can be explained with only slight local misorienations in the crystal lattice [12].…”
Section: Introductionmentioning
confidence: 97%